La promoción de la salud y sus aportes a la educación en alimentación y nutrición (2005)
ABSTRACT: The epidemiological profile, the reforms to the General System of Social Security and the economic, political and social context in our country present health professionals new challenges in order to promote health. The promotion of health has to be understood as the summatory of the health services, social and productive sectors and the sanitary authorities actions aiming to improve health conditions, framed within models derivated from the dynamics of the communities where communal empowerment and human development help to strenghten the health and nutritional educational processes.